Pradaria mineira: a influência do prairie style na arquitetura residencial unifamiliar de Belo Horizonte - Jose Julio Rodrigues Vieira (2009)
The aim of the present study is to investigate the occurrence, through the course of the decades of 1930, 40 and 50, of a single-family residential architecture in Belo Horizonte influenced by North-American architect Frank Llloyd Wright, in what concerns his architecture described as Prairie Style. After determining the situation of the architecture of the Prairie Style and its role in the evolution of single-family residential architecture in the United States, the research goes on to study the way that its penetration took place in Brazil, and more specifically in Belo Horizonte. At this point the importance of American movies and architecture magazines is considered, as well as the formal study ofarchitecture in the city and its relationship with Rio de Janeiro and São Paulo, the main academic centers of the country. A detailed study of buildings in Belo Horizonte is then presented, identifying certain features typical of the style and its importance in the context of the evolution of residential architecture in the city. From the conclusions obtained, the possibility of determining an ensemble from the most important examples studied is considered, aiming the development of strategies for its preservation.